A mathematical model to investigate the effect of misdiagnosis and wrong treatment in the co-circulation and co-infection of Malaria and Zika virus disease - Duru, Emmanuel Chidiebere; Anyanwu, Michael C.; Ezike, Mbah Godwin Christopher (Fırat Evirgen, 2025)
Malaria and Zika virus disease are infectious diseases transmitted among humans through the bites of an infectious female Anopheles and Aedes aegypti mosquitoes, respectively. In areas where the two diseases co-circulate, their coinfection is possible. Both diseases exhibit similar characteristic symptoms, hence one can be misdiagnosed as the other. In this work, we use a system of nonlinear ordinary differential equations to present a new model for the coinfection of the two diseases. The dynamics of the individual diseases are also shown. The disease-free equilibrium (DFE) points of the individual diseases are seen to be both locally and globally asymptotically stable when their respective basic reproduction numbers are less than one. But, the coinfection-free equilibrium (CFE) is seen to be only locally asymptotically stable when the basic reproduction number $\mathcal{R}_{mz}$ is less than one, and unstable otherwise. However, the CFE may not be globally stable when \(\mathcal{R}_{mz}
Keywords: Biological Mathematics; Biyolojik Matematik; Applied Mathematics (Other); Uygulamalı Matematik (Diğer)